Meningkatkan kompetensi profesional guru dengan pelatihan pembelajaran matematika realistik - Usman Mulbar; Ilham Minggi; Ahmad Zaki (Universitas Negeri Makassar, 2020)
The PKM program is carried out with the method of providing training and guidance to participants on realistic mathematics learning to improve teacher competence in implementing learning with the aim of (1) to increase knowledge about realistic mathematics learning, (2) participants can implement realistic mathematics learning in the learning process, and (3) participants can disseminate or disseminate realistic mathematics learning knowledge. The main target audience for the PKM Program activities are school supervisors, school principals and school teachers in Tinggimoncong sub-district, Gowa district, South Sulawesi province. The results obtained in PKM program activities are increasing knowledge and realistic mathematics learning concepts of PKM program participants, increasing the skills of developing realistic mathematics learning skills in PKM program participants, PKM program participants can make examples and arrange realistic mathematics learning activities in learning classes, and PKM program participants can implementing realistic mathematics learning in learning in schools. Other results obtained were increased motivation of participants in knowing realistic mathematics learning materials and high enthusiasm of participants in disseminating or disseminating PKM program results, especially realistic mathematics learning materials. Outputs of PKM activities are (1) increasing participant's knowledge regarding activity materials, (2) scientific articles published at national seminars, and (3) publications on PKM implementation on online media.